The effectiveness of teaching according to the logical thinking skills in the scientific achievement of the fourth graders in the subject of chemistry - Omran Khudair, Alia; Hussein Ali, Saeed; Kazem Murad, Amna (International Journal of Psychosocial Rehabilitation, 2020)
research aims to identify the effectiveness of teaching according to the logical thinking skills in the achievement of fourth-grade students in science in the subject of chemistry, and to verify the goal, the researcher developed the null hypothesis that states: There is no statistically significant difference at the level of significance (0.05) between the average grades of the experimental group students who will study According to the logical thinking skills and average grades of the control group students who will study according to the usual method in the chemistry test, and in order to verify it, he applied his experience in the second semester of the school year (2019-2020 M), IT formed the research sample of 40 students of the students grade the fourth scientific in the secondary FAO Girls Was distributed n randomly into two groups of (20) student of each group, and it has been rewarded with the two groups in the following variables: :chronological age, IQ test , score the second course of the previous academic year in material chemistry , and test the previous information , and in the light of The relative importance of the content and behavioral purposes. An achievement test consisting of paragraphs of these 27 items of multiple choice type and nine paragraphs of the essay type was built , and the researcher verified the characteristics of the psychometric test for the test . The experiment continued (10) as I said, and at the end of the experiment, a summative test was applied to the two groups and then analyzed The results showed the superiority of the students of the experimental group of Latte studied n terms of IQ skills of logical thinking on the control group of Latte studied in the usual way in the collection variable school.